2012
DOI: 10.1093/nar/gks368
|View full text |Cite
|
Sign up to set email alerts
|

KH domains with impaired nucleic acid binding as a tool for functional analysis

Abstract: In eukaryotes, RNA-binding proteins that contain multiple K homology (KH) domains play a key role in coordinating the different steps of RNA synthesis, metabolism and localization. Understanding how the different KH modules participate in the recognition of the RNA targets is necessary to dissect the way these proteins operate. We have designed a KH mutant with impaired RNA-binding capability for general use in exploring the role of individual KH domains in the combinatorial functional recognition of RNA targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 42 publications
4
97
1
Order By: Relevance
“…4C and Fig. S4D, the interaction of KSRP mutants with transfected myogenin 3′UTR or endogenous KSRP mRNA targets (GNAS and CTNNB1, also known as β-catenin) occurred according to the previously described mode with KH2, KH3, and KH4 playing the major role in the RNA recognition and KH1 resulting dispensable (28,29). The interaction of KSRP with H19 was unaffected by mutations in KH4 but was impaired not only by mutations in KH2 and 3 but also in KH1 (Fig.…”
Section: H19 Silencing In Undifferentiated C2c12 Cells Promotes Myogementioning
confidence: 65%
See 2 more Smart Citations
“…4C and Fig. S4D, the interaction of KSRP mutants with transfected myogenin 3′UTR or endogenous KSRP mRNA targets (GNAS and CTNNB1, also known as β-catenin) occurred according to the previously described mode with KH2, KH3, and KH4 playing the major role in the RNA recognition and KH1 resulting dispensable (28,29). The interaction of KSRP with H19 was unaffected by mutations in KH4 but was impaired not only by mutations in KH2 and 3 but also in KH1 (Fig.…”
Section: H19 Silencing In Undifferentiated C2c12 Cells Promotes Myogementioning
confidence: 65%
“…All plasmids were sequenced before their use. pcDNA3-Flag-KSRP, pCMV-TAG2B-KSRP, pCMV-TAG2B-KSRP(S193D), pCMV-TAG2B-KH1GDDG, pCMV-TAG2B-KH2GDDG, pCMV-TAG2B-KH3GDDG, pCMV-TAG2B-KH4GDDG, pcDNA-3-myrAKT2, pcDNA3-MKK6EE, pcDNA3-EXOSC2, and pcDNA3-EXOSC5 plasmids were described elsewhere (13,14,21,28,46). Adenoviral vector expressing myristoylated AKT2 and the respective negative control were from Vector Biolabs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects were less pronounced, both K571L and K571Q also resulted in losses of repression in vivo and weakened K D values in vitro. Hollingworth et al reported that a GDDG double mutation in KH-type splicing regulatory protein (KSRP) impairs nucleic acid binding without compromising KH domain stability (40). The absence or augmentation of the canonical GxxG sequence appears to be a hallmark of impairment of RNA binding (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the RNA binding function of the KH domains of NusA, GLD-1, Sam68, and heterogeneous nuclear RNP K were all severely impeded upon mutating the first glycine in the GXXG motif to an aspartate (24 -27). In fact, a recent study showed the feasibility of double mutating the GXXG loop, namely from GXXG to GDDG, in the KH domain of the RNAbinding protein KSRP and the KH3 and KH4 domains of IMP1, as an effective tool for the investigation of the nucleic acidbinding function of individual KH domains (28).…”
Section: The Ability Of Its Four Heterogeneous Nuclear Rnp-k-homologymentioning
confidence: 99%